(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
هدفت الدراسة إلى التعرف على واقع ممارسة إدارة البيئة الصفية من قبل الطلبة المعلمين ، من وجهة نظر الطلبة المعلمين أنفسهم . تم استخدام المنهج الوصفي بالعينة العشوائية التي تكونت من (104)طالباً وطالبةً من كلية التربية الثانية/ معلم صف في محافظة طرطوس للعام الدراسي 2013/2014 , وتم بناء استبانة مكونة من (66) فقرة تقيس ممارسات إدارة البيئة الصفية, موزعة على خمسة محاور هي: حل مشكلات التلامذة و التواصل و تنظيم البيئة المادية وإدارة وقت الحصة الدراسية و القواعد والإجراءات الصفية . تم استخدام التحليل الإحصائي المناسب في ضوء ما تم جمعه من المعلومات والبيانات باستخدام برنامج حزمة العلوم الاجتماعية (spss) , وقد أظهرت الدراسة أن ممارسة الطلبة المعلمين لإدارة البيئة الصفية من وجهة نظرهم جاءت بدرجة جيدة للأداة ككل , وقد احتل محور تنظيم البيئة المادية المرتبة الأولى بينما احتل محور حل مشكلات التلامذة المرتبة الأخيرة , كما أظهرت الدراسة وجود فروق دالة إحصائيا حول واقع ممارسة إدارة البيئة الصفية تعزى لمتغير الجنس لصالح الذكور , ولم تظهر الدراسة فروقا دالة إحصائيا تعزى لمتغير نوع الشهادة الثانوية . The study aims at identifying the reality of the student teacher practicing management of the classroom environment , from their perspective . Descriptive approach has been used in random sampling, which consists of (104) male and female students of the Second Faculty of Education in Tartous City. The researcher prepared a questionnaire composed of (66) paragraphs measuring the practicing of management classroom environment, distributed into five approaches which are: Solving the problems of the students, communication, organizing the physical environment, the classroom time management, classroom rules and procedures. In the light of the information and data that have been collected, statistical analysis (spss) was used. The results showed that classroom environment management from the viewpoint of the students themselves got a good grade of questionnaire . The field of organization of the physical environment got a first rank while the field of solving the problems of the students got the last rank. There are statistically significant differences about the reality of practicing the management of classroom environment in favor of males, and there is no statistically significant differences in the type of secondary school certificate.